EFFECTIVE GENERAL HEALTH PRACTITIONER LEADERSHIP AND MANAGEMENT STRATEGIES - Ali Hamad F. Alsuwais; Salem Mushari Saleh Aldughman; Shabib Rashed Aldosri; Mesfer Mohammed Althafir; Fahad Mohsen Alhurayyis; Eid Khalaf Al-Dhafiri; Lamia marzoq almutiri; Abdulrhman Thani Alanazi; Somaya Naseer Kandiri; Nouf Abdulrahman Mubarak (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The present research seeks to investigate the significance of proficient leadership and management strategies within the nursing profession. It emphasizes the substantial influence of nurse management practices on the nursing workforce, job satisfaction, and patient results. This research highlights the importance of identifying the characteristics of an exemplary nursing leader and fostering effective leadership strategies. This study investigates several leadership theories, including transformational management, resonant leadership, and genuine leadership, within the nursing profession. The study highlights the association between relational leadership styles and positive outcomes for nurses, such as higher professional competence, decreased burnout, heightened work satisfaction, and improved well-being. The paper highlights the impact of organizational elements, such as the makeup of staff, the availability of resources, and the models of leadership, on the successful implementation of leadership. This statement highlights the significance of strategy development and decision-making protocols within the realm of nursing leadership. Moreover, the research emphasizes the significance of nursing leadership in advancing digital and technical interventions, remote workforce management, and problem-solving within the healthcare industry. Trainers are needed to improve the leadership skills and abilities of nurse leaders. The conclusion of this study underscores the need of using a methodical strategy to gathering and assessing nursing leadership strategies, as well as their effects on organizational, nursing personnel, and patient results. It promotes a comprehensive assessment to determine future research needs and enhance the efficacy of nursing leadership.